Estimating the economic damages from the Penglai 19-3 oil spill to the Yantai fisheries in the Bohai Sea of northeast China. (December 2015) - Pan, Guangchen; Qiu, Shengyao; Liu, Xin; Hu, Xiaoke
Abstract: The Penglai 19-3 oil spill was one of the worst pollution incidents to occur along the Chinese coastline in terms of both the size of the spill and the area polluted with 840 square kilometers of previously clean coastal waters significantly degraded. The current study estimated economic damages from the spill in two economic sectors, the Yantai fishery and the Yantai mariculture business. Estimates revealed that the ecological damage to fisheries and mariculture affected local crustacean species, shellfish, algae, sea cucumbers and sea urchins much more seriously than the adult fish, partly because fish are very mobile and partly because of the submarine nature of the PL19-3 spill. Toxic oil floating on the sea surface created less of a threat to fish, when comparing them with benthos and algae. Therefore, the economic losses were mainly caused by a reduction in the productivity of crustaceans, shellfish, algae, sea cucumbers and sea urchins, totaling as much as 1 CNY1239.5 million for 63, 044 t in weight. Together with the loss in the fishing sector (i.e., CNY16.85 million), the total economic losses were about CNY12.56 billion.